(untitled) (Sebha University Conference Proceedings, 2025)
Geothermal energy used for heat and electrical power production; is part of concept for past many years, geothermal plants enable of renewable electricity production amounts with permanent production capacity. Therefore, our work is oriented towards the simulation of behavior power plant according to the temperature and pressure. objective of this work is to compare produced power from geothermal resources , function of geothermal temperature and organic fluid Butane, R245fa, and R11, used for organic Rankine cycle of thermal plant. For this, we choose "Thermoptim" software that allows in particular to thermodynamic cycles model, we introduce the necessary parameters and constraints, simulations and sensitivity studies to compare the results and represent curves trend. we compare different working fluids from energy performance, that is to say the production of electricity from geothermal low-temperature source, to determine reinjection temperature of geothermal water outlet of power plant cycle and evaluating recovered powers of different geothermal temperatures. Obtained results show that optimal power for maximum of 20kg/s, for Butane , is function of geothermal temperature resource; so for 90°C for geothermal temperature we can’t produce more than 1MW, for 100°C power can be 1.3 MW; 120°C; it can produce 1.6MW, and 1.8MW can be produced for geothermal resource temperature of 140°C. And rei njected temperature is not very different for resource temperature; and this can be very important because this difference can be gained slowly and easy without a lot of loss.